Imagem ancestral brasileira: análise das imagens rupestres mineiras da Tradição Planalto à luz de uma teoria da imagem - (10.000 - 3.000 anos A.P.) - Viviani, Ana Elisa Antunes (2020)
This research aims to analyze the figurative forms on the rock surfaces in the Planalto tradition, Minas Gerais, Brazil, which dates from 10,000 to 3,000 years BP, located in three regions of the State of Minas Gerais: Lagoa Santa, Santana do Riacho and Diamantina (in Serra do Espinhaço). The investigation sought to understand the reasons that would have led to the change in the formal features of these parietal wall and cave images over time, from more figurative to more stylized as well as thematic features. In earlier times, this feature-changing phenomenon boiled down to isolated images of deer and fish to which other beings, including human figures, were later added, gaining seemingly narrative contexts. To this end, this work relied on research developed in Brazil since the 1970s that has analyzed the archaeological remains of these three regions, which allowed us to re-elaborate the physical and psychological environment of the creation of Minas Gerais parietal paintings. Rock art is traditionally investigated by archeology, which interprets it according to the methodological accuracy and theories of its scientific field. Here, the goal is to analyze parietal paintings using Hans Belting's Anthropology of Image, which is an approach that understands any image as a result of a relationship between the human body and the kind of medium that conveys the image. In turn, given the importance that the environment or the medium assumes under this new point of view, the Theory of Culture of semiotician Ivan Bystrina is cast as complementary analytical support for the investigation. According to Bystrina, images belong to a human existential reality different from the instrumental one, since it emerges from the moments of imagination and dreams, and also from the psychopathological variants and states of ecstasy that humans might experience through life. The research included visits to the region of Lagoa Santa and Santana do Riacho for photographic work, which allowed us to reflect on the relationship between the experiences of proximity and distance provided by rock art, similar to the way Walter Benjamin refers to the exhibition value of the works of art. Other rock art reproductions from reference material and websites were also used. Finally, the analysis was inspired by Aby Warburg's thoughts on how to organize and study images so that new and authentic reflections on them could be elaborated. Thus, it was possible to realize that the images from the Paleoindian and Archaic Period in the Planalto tradition, located in Minas Gerais, depicted not only animals and other beings but also mobilized dreams and memories that, over time, were being shaped on the rock wall in the form of mythical narratives